Bi-sn-x alloy melt-seal composite media, wellbore repair methods and systems

CN122941382APending Publication Date: 2026-10-20XI'AN PETROLEUM UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611158245.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

传统井筒修复和封堵手段主要包括挤水泥、化学堵剂、机械桥塞、可膨胀封隔器等,但上述方法在面对宽度50μm~500μm量级的微裂缝、微环空时,存在以下突出缺陷:第一,水泥浆颗粒粒径通常大于10μm,且水化体系易在窄缝中桥堵失效,难以进入并填实微米级通道;第二,化学堵剂(如树脂、凝胶)在高温(120℃~200℃)、高矿化度、含H2S/CO2的井下环境中长期稳定性差,易发生降解、收缩与窜流;第三,机械工具难以处理不规则形貌的微环空与套管外侧亏空;第四,废弃井永久封堵对封堵体的耐久性要求长达100年~1000年量级,常规材料难以满足

Benefits of technology

本发明的Bi-Sn-X合金熔封复合介质中,包括氧化液和还原液,氧化液中的H2O2与还原液中的亚硫酸盐发生氧化还原反应的产物仅为Na2SO4/NaHSO4水溶液与水,无N2、O2、H2、CO2等气体释放,实现了近零产气,避免了气体在熔融Bi-Sn-X封堵体中形成孔洞,封堵体孔隙率可控制在0.5%以下;并且本发明通过引入CaO微胶囊粉末和/或MgO微胶囊粉末作为缓释膨胀热源材料,与氧化液、还原液以及Bi-Sn-X合金复合材料共同构建了氧化还原快速升温、水化缓释保温、相变金属凝固膨胀、氢氧化物水化膨胀四级协同封堵机制,最终形成金属-无机固相复合封堵体,封堵强度高、密封压差可达50MPa以上。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a Bi-Sn-X alloy sealing composite medium, a wellbore repair method, and a system, belonging to the field of oil and gas well plugging and repair technology. The Bi-Sn-X alloy sealing composite medium includes an oxidizing liquid, a reducing liquid, a Bi-Sn-X alloy composite material, and a slow-release expansion heat source material. The oxidizing liquid is composed of hydrogen peroxide, a corrosion inhibitor, a thickener, a stabilizer, and water. The reducing liquid is composed of sulfite, a scale inhibitor, a pH buffer, a chelating agent, and water. The Bi-Sn-X alloy composite material is obtained by coating a Bi-Sn-X alloy core with a metal oxide layer, an organic film, and a reinforcing film from the inside out. X is selected from one or more of In, Ag, Cu, Zn, and Sb. Heat is released through a redox reaction between hydrogen peroxide and sulfite, preventing the formation of pores in the gas during the plugging process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of oil and gas well plugging and repair technology, specifically involving Bi-Sn-X alloy fusion sealing composite medium, wellbore repair methods and systems. Background Technology

[0002] In engineering practices such as oil and gas extraction, underground gas storage, compressed air energy storage (CAES), and carbon dioxide geological sequestration, problems such as cement sheath failure, casing corrosion and perforation, micro-annular leakage, and formation void channel flow seriously threaten wellbore integrity and formation isolation safety. Traditional wellbore repair and plugging methods mainly include cementing, chemical plugging agents, mechanical bridging plugs, and expandable packers. However, these methods have the following prominent drawbacks when dealing with microcracks and microannulus with widths ranging from 50μm to 500μm: First, cement slurry particles are usually larger than 10μm in diameter, and the hydration system is prone to bridging failure in narrow cracks, making it difficult to enter and fill micron-sized channels; Second, chemical plugging agents (such as resins and gels) have poor long-term stability in downhole environments with high temperatures (120℃~200℃), high mineralization, and H2S / CO2 content, and are prone to degradation, shrinkage, and crossflow; Third, mechanical tools are difficult to handle irregularly shaped microannulus and voids on the outside of the casing; Fourth, permanent plugging of abandoned wells requires the plugging body to have a durability requirement of 100 to 1000 years, which conventional materials cannot meet.

[0003] To address the aforementioned issues, researchers have developed a Bi-Sn-X ternary low-melting-point alloy. This alloy (where X is one or more elements such as In, Ag, Cu, Zn, and Sb) has a continuously adjustable melting point within the range of 60℃ to 180℃ and possesses the following unique advantages: it exhibits a volume expansion effect of 0.1% to 3.3% during solidification, enabling active mechanical sealing between the surrounding rock and the casing; its liquid metal has excellent fluidity, allowing it to penetrate submicron-level channels; its metallic state is thermally and electrically conductive, dense, and does not age over long periods, with a theoretical lifespan on the order of millennia; and it exhibits low reactivity with H2S and CO2, resulting in durability far exceeding that of cement and polymer materials. However, the key bottleneck for the downhole application of Bi-Sn-X alloys lies in how to generate sufficient heat in situ, controllably, and safely in the target formation to melt the alloy material from a solid to a liquid state, while avoiding the formation of pores by gaseous byproducts, corrosion of the alloy by oxidizing media, and premature reactions leading to surface or wellbore accidents throughout the melting-flow-solidification process. The existing downhole chemical exothermic systems (such as NaNO2-NH4Cl, magnesium-acid, aluminum-alkali, magnesium-water, alumina-water, etc.) generally have the following problems: (1) The NaNO2-NH4Cl system will release a large amount of N2 gas, and the reaction formula is NaNO2+NH4Cl→NaCl+N2↑+2H2O. The gas will form pores in the molten metal body, destroying the tightness of the sealing body; (2) The metal-acid system will release H2 gas, and the strong acid medium will severely corrode the Bi-Sn-X alloy and casing; (3) The metal-alkali system also produces gas, and the reaction is violent and difficult to control; (4) Although the hydration exothermic system (CaO / MgO+H2O) has no gas by-products, the unit heat density is low, and the reaction rate is limited by hydration kinetics, making it difficult to meet the requirements of rapid alloy melting.

[0004] Therefore, there is an urgent need for a downhole liquid chemical heat source system with near-zero gas production, sufficient heat density, controllable reaction, good compatibility with Bi-Sn-X alloy and casing materials, and low cost, in order to solve the engineering bottleneck of in-situ melting-solidification sealing of Bi-Sn-X liquid metal. Summary of the Invention

[0005] To address the problems in the prior art, this invention provides a Bi-Sn-X alloy fusion sealing composite medium, a wellbore repair method, and a system. Using the Bi-Sn-X alloy fusion sealing composite medium provided by this invention can effectively solve the engineering bottleneck of in-situ melting-solidification sealing of Bi-Sn-X liquid metal.

[0006] To achieve the above objectives, the present invention employs the following technical solution: A Bi-Sn-X alloy sealing composite medium includes an oxidizing liquid, a reducing liquid, a Bi-Sn-X alloy composite material, and a slow-release expansion heat source material.

[0007] The oxidizing solution is composed of the following components by mass percentage: 20%~50% hydrogen peroxide, 0.2%~1.5% corrosion inhibitor, 0.3%~1.0% thickener, 0.05%~0.3% stabilizer, and the remainder is water, totaling 100%.

[0008] The reducing solution consists of the following components by mass percentage: 20%~50% sulfite, 0.2%~1.0% scale inhibitor, 0.5%~2.0% pH buffer, 0.1%~0.5% chelating agent, and the remainder is water, totaling 100%.

[0009] Bi-Sn-X alloy composite material consists of a Bi-Sn-X alloy core as the core body, with a metal oxide layer, an organic film, and a reinforcing film sequentially coated from the inside out. X is selected from one or more of In, Ag, Cu, Zn, and Sb. The melting point of the Bi-Sn-X alloy composite material is 80℃~160℃. It should be noted that the metal oxide layer can be a surface oxide layer naturally formed during the preparation, cleaning, drying, or short-term air passivation of the Bi-Sn-X alloy core, or it can be formed through low-temperature oxidation treatment. Therefore, the metal oxide layer does not necessarily require a separate and complex preparation process.

[0010] The slow-release expansion heat source material is CaO microcapsule powder and / or MgO microcapsule powder.

[0011] The molar ratio of anion to hydrogen peroxide in sulfite is 1.02~1.10:1. In this invention, the reducing agent is slightly in excess to ensure that the hydrogen peroxide is completely consumed and to avoid residual oxidant corroding the Bi-Sn-X alloy and the bushing. The initial pH of the reaction system is controlled within the range of 6~9 by a pH buffer, and the pH buffer maintains the system at near-neutral to weakly alkaline levels during the reaction.

[0012] The amount of Bi-Sn-X alloy composite material added is 10% to 30% of the total mass of the oxidizing and reducing solutions; more preferably, the amount of Bi-Sn-X alloy composite material added is 15% to 25% of the total mass of the oxidizing and reducing solutions. In this invention, the amount of Bi-Sn-X alloy composite material added is specifically calculated based on the target sealing layer volume, microcrack / microannular porosity (typically 5% to 15%), and solidification expansion rate; for example, when the sealing length is 30m and the casing inner diameter is 139.7mm, the alloy dosage is approximately 350kg to 500kg.

[0013] The amount of slow-release expansion heat source material added is 5% to 20% of the total mass of the oxidizing liquid and the reducing liquid.

[0014] In this invention, the corrosion inhibitor protects the casing and alloy from oxidative corrosion by H2O2, with a corrosion weight loss rate of <0.1wt% (based on the oilfield corrosion inhibitor standard SY / T 5405). The thickener regulates the mixing reaction rate of the oxidizing and reducing fluids, thereby delaying the arrival time of the peak temperature, and utilizes its shear-thinning properties to suspend the Bi-Sn-In alloy composite material and improve its carrying capacity. The stabilizer inhibits the decomposition of H2O2 to prevent premature surface reaction. The scale inhibitor prevents BaSO4 / CaSO4 scaling, the pH buffer maintains the pH of the reaction system at 6-9 to avoid acidic corrosion or alkaline precipitation, and the chelating agent chelates polyvalent ions. It should be noted that no component used in this invention can be omitted; omitting any component will result in uncontrollable reactions, high corrosion risk, and scaling and wellbore blockage.

[0015] In a preferred embodiment of the present invention, the organic film in the Bi-Sn-X alloy composite material is polyethylene wax or paraffin wax; the reinforcing film is an epoxy resin film or a polylactic acid film.

[0016] In a preferred embodiment of the present invention, the Bi-Sn-X alloy core is one or more of the following: granular Bi-Sn-X alloy core, rod-shaped Bi-Sn-X alloy core, microspherical Bi-Sn-X alloy core, and fibrous Bi-Sn-X alloy core; the particle size of the granular Bi-Sn-X alloy core is 50 μm to 2000 μm; the aspect ratio of the rod-shaped Bi-Sn-X alloy core is 3 to 20; the diameter of the microspherical Bi-Sn-X alloy core is 100 μm to 500 μm; and the diameter of the fibrous Bi-Sn-X alloy core is 100 μm to 300 μm, with a length of 1 mm to 5 mm. In a preferred embodiment of the present invention, the Bi-Sn-X alloy core is composed of the following components by mass percentage: 60%~80% granular Bi-Sn-X alloy core, 10%~30% rod-shaped Bi-Sn-X alloy core, and the remainder is fibrous Bi-Sn-X alloy core, totaling 100%. The Bi-Sn-X alloy core is graded with various morphologies to form a tightly packed structure in the suspension, improving the particle volume fraction and suspension stability. The granular shape facilitates seepage filling of microcracks, while the rod-shaped and fibrous shapes can form a bridging framework in wider cracks, reducing particle settling and crossflow losses before melting, and improving the overall strength of the sealing body.

[0017] In a preferred embodiment of the present invention, the corrosion inhibitor is an imidazoline quaternary ammonium salt or a benzotriazole, wherein the imidazoline quaternary ammonium salt exhibits a corrosion inhibition rate of >95% in H2S / CO2 environments. The thickener is partially hydrolyzed polyacrylamide or xanthan gum; xanthan gum retains >80% viscosity at a mineralization of 45000 mg / L and a temperature of 200°C. The stabilizer is sodium pyrophosphate or sodium stannate.

[0018] In a preferred embodiment of the present invention, the sulfite is one or more of sodium sulfite, sodium bisulfite, and sodium metabisulfite; the scale inhibitor is aminotrimethylenephosphonic acid or ethylenediaminetetramethylenephosphonic acid, which has a scale inhibition efficiency >90% for calcium and barium ions; the pH buffer is a combination of sodium dihydrogen phosphate and disodium hydrogen phosphate or a combination of boric acid and borax; phosphate as a pH buffer stabilizes the H2O2 system, while boric acid as a pH buffer has the advantage of high temperature resistance (>150°C). The ratio of the two buffer salts used in the pH buffer of the present invention is adjusted according to the target pH value to maintain the system pH in the range of 6 to 9. More preferably, the mass ratio of sodium dihydrogen phosphate to disodium hydrogen phosphate is 1:0.5 to 1:2, and the mass ratio of boric acid to borax is 1:0.5 to 1:2. The chelating agent is tetrasodium ethylenediaminetetraacetate or aminotriacetic acid. Tetrasodium ethylenediaminetetraacetate has a chelation constant logK > 16, which can effectively remove polyvalent ions.

[0019] This invention also provides a wellbore repair method using the aforementioned Bi-Sn-X alloy fusion sealing composite medium. The repair method involves: injecting a pre-flushing fluid containing chelating agents and scale inhibitors into the target formation to remove oil and polyvalent metal ions; after cleaning, transporting the Bi-Sn-X alloy composite material to the target sealing formation; mixing a reducing agent and a slow-release expansion heat source material to form a mixed solution; transporting the mixed solution and an oxidizing agent to the bottom of the well for mixing, during which the reducing agent and oxidizing agent in the mixed solution undergo an oxidation-reduction reaction releasing heat, as does the slow-release expansion heat source material, causing the Bi-Sn-X alloy core to melt and form a Bi-Sn-X alloy molten liquid. Driven by downhole pressure differential and gravity, the Bi-Sn-X alloy molten liquid seeps into the wellbore area to be repaired, solidifies and expands to form a composite sealing body, completing the sealing. It should be noted that CaO and / or MgO in the slow-release expansion heat source material will react with water. However, in this invention, the CaO and / or MgO have a microcapsule coating layer, which can isolate or delay the entry of moisture into the particle interior. Therefore, the slow-release expanding heat source material does not significantly prematurely hydrate when premixed with the reducing solution for a short time; when it enters the well, under the influence of increased temperature, shear disturbance, and increased residence time, the coating layer gradually ruptures, softens, or dissolves, and only then does CaO / MgO react with water and release heat. Therefore, even after the slow-release expanding heat source material is premixed with the reducing solution, there is no problem of premature reaction of CaO and / or MgO.

[0020] In a preferred embodiment of the present invention, the method for conveying the Bi-Sn-X alloy composite material is as follows: the Bi-Sn-X alloy composite material is prepared into an alloy suspension in a xanthan gum aqueous solution, wherein the mass concentration of the Bi-Sn-X alloy composite material in the alloy suspension is 60%~65%; the discharge rate of the alloy suspension is 0.15~0.20 m³ / s. 3 The reason for using xanthan gum aqueous solution as the carrier fluid in the alloy suspension is that xanthan gum has excellent shear-thinning properties, resulting in low viscosity during pumping, strong suspension capacity during settling, temperature and salt resistance (bottom-hole salinity 45000 mg / L), good compatibility with H2O2, no oxidative degradation, and biodegradability, making it environmentally friendly. The discharge rate of the oxidizing fluid is 0.10~0.13 m³ / min. 3 The flow rate of the mixed solution is 0.11~0.16 m³ / min. 3 / min. The above displacement is the actual pumping displacement of the surface high-pressure pump, which reaches the downhole static mixer through the coaxial dual-liquid continuous tubing to achieve a 1:1.1 volume ratio mixing.

[0021] As a preferred embodiment of the present invention, the wellbore repair scenarios include cement sheath microcrack repair, casing-cement sheath microannulus repair, casing perforation repair, permanent sealing of abandoned wells, underground gas storage sealing layer repair, and compressed air energy storage wellbore sealing repair. More preferably, for acidic gas wells with H2S concentration greater than 1 vol% or CO2 concentration greater than 1 vol%, the Bi-Sn-X alloy core in the Bi-Sn-X alloy composite material is selected from a Bi-Sn-Sb system or a Bi-Sn-Ag system, and the corrosion inhibitor is selected from an imidazoline quaternary ammonium salt type resistant to H2S.

[0022] In this invention, accelerated corrosion tests (180℃, 20MPa, 90 days) extrapolate the corrosion rate of Bi-Sn-X in an H2S / CO2 environment to <0.01mm / a. The inorganic phases Ca(OH)2 / Mg(OH)2 / Na2SO4 have extremely low solubility in groundwater (<0.1g / L). Based on reference to the life assessment methods for abandoned well plugging materials (API RP 65-3 and NORSOK D-010), the theoretical durability of the final composite plugging body is 500~1000 years.

[0023] The present invention also provides a wellbore repair system, comprising: The coaxial dual-fluid coiled tubing is installed inside the casing of the wellbore and extends along the inside of the casing to above the target sealing section downhole. The coaxial dual-fluid coiled tubing is formed by coaxially sleeved outer and inner tubes. An annular channel is formed between the inner wall of the outer tube and the outer wall of the inner tube, and an inner tube channel is formed inside the inner tube. A suspension channel is provided on one side of the outer tube wall. A blowout preventer is installed above the coaxial dual-fluid coiled tubing.

[0024] An oxidizing liquid storage tank, located on the ground, is used to store oxidizing liquid. The outlet of the oxidizing liquid storage tank is connected to the first inlet of the high-pressure injection pump group via a first pipeline. The first outlet of the high-pressure injection pump group is connected to the annulus channel via a wellhead blowout preventer. A reducing liquid storage tank, located on the ground, is used to store a mixed liquid. The outlet of the reducing liquid storage tank is connected to the second inlet of the high-pressure injection pump group via a second pipeline. The second outlet of the high-pressure injection pump group is connected to the inner pipe channel via a wellhead blowout preventer. An alloy suspension storage tank, located on the ground, is used to store alloy suspension. The outlet of the alloy suspension storage tank is connected to the third inlet of the high-pressure injection pump group via a third pipeline. The third outlet of the high-pressure injection pump group is connected to the suspension channel via a wellhead blowout preventer.

[0025] The downhole static mixer is detachably connected to the bottom of the coaxial dual-fluid continuous tubing. The downhole static mixer contains, from top to bottom, static mixing spiral blades, a delayed mixing chamber, a soluble diaphragm, and an outlet nozzle. The flowback line has one end located in the wellbore below the target sealing section, and the other end extends upward along the inside of the casing, connecting to the surface treatment components through the wellhead blowout preventer.

[0026] Compared with the prior art, the present invention has the following beneficial effects: The Bi-Sn-X alloy fusion sealing composite medium of the present invention includes an oxidizing liquid and a reducing liquid. The oxidation-reduction reaction between H2O2 in the oxidizing liquid and sulfite in the reducing liquid produces only Na2SO4 / NaHSO4 aqueous solution and water, with no release of gases such as N2, O2, H2, and CO2, achieving near-zero gas production and avoiding the formation of pores in the molten Bi-Sn-X plugging body. The porosity of the plugging body can be controlled below 0.5%. Furthermore, the present invention introduces CaO microcapsule powder and / or MgO microcapsule powder as a slow-release expansion heat source material, which, together with the oxidizing liquid, reducing liquid, and Bi-Sn-X alloy composite material, constructs a four-level synergistic plugging mechanism of rapid heating during oxidation-reduction, slow-release heat preservation during hydration, solidification expansion of phase change metal, and hydration expansion of hydroxide, ultimately forming a metal-inorganic solid-phase composite plugging body with high plugging strength and a sealing pressure difference of over 50 MPa.

[0027] In this invention, based on the total mass of hydrogen peroxide and sulfite (Na2SO3) participating in the reaction, the heat released by the reactants is approximately 2.5 MJ / kg to 3.5 MJ / kg, which can meet the melting window requirement of 80℃ to 160℃. The heat density is sufficient and controllable. The reaction rate can be controlled by multiple means such as pH buffer, concentration of hydrogen peroxide and sulfite, thickener, and slow-release expansion heat source material. The peak temperature lasts for 30 min to 180 min.

[0028] The H2O2, sulfite (Na2SO3 or NaHSO3), CaO and MgO used in this invention are all bulk industrial products, with a comprehensive raw material cost of about 2 yuan / kg to 6 yuan / kg, which is low and far lower than conventional chemical plugging agents.

[0029] The oxidizing and reducing liquids used in this invention are both pumpable liquids. The Bi-Sn-X alloy composite material can be made into a suspension for transportation. It is fully compatible with existing operating equipment such as coiled tubing, coaxial tubing strings, and downhole static mixers. From an engineering implementation perspective, this invention has extremely high operability.

[0030] The wellbore repair system provided by this invention isolates the required liquid through a three-channel system, mixes it in a downhole static mixer, and employs multiple measures such as multi-layer coating of the Bi-Sn-X alloy core surface and a slight excess of reducing agent. This achieves a process sequence of reaction followed by melting. These multiple measures ensure that H2O2 does not directly contact the Bi-Sn-X alloy core, resulting in a corrosion weight loss rate of less than 0.1 wt% for the Bi-Sn-X alloy core. The sealing body ultimately formed by this invention is composed of a metallic phase Bi-Sn-X and an inorganic phase Ca(OH)2 / Mg(OH)2 / Na2SO4, with a theoretical service life of 500 to 1000 years. Based on API RP 65-3 / NORSOK D-010, it exhibits resistance to H2S / CO2 corrosion <0.01 mm / a, meeting national standards for permanent sealing. It demonstrates excellent long-term durability and is particularly suitable for permanent sealing of abandoned wells and long-term sealing requirements in geological energy storage. Attached Figure Description

[0031] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0032] Figure 1 This is a schematic diagram of the overall process flow of the near-zero gas production dual-liquid heat source-Bi-Sn-X in-situ melting plugging agent system of the present invention.

[0033] Figure 2 This is a schematic diagram of the longitudinal section of a coaxial dual-fluid continuous tubing and a downhole static mixer.

[0034] Figure 3 This is a schematic diagram of the microstructure of the coating film on the surface of the Bi-Sn-X alloy core.

[0035] Figure 4 This is a schematic diagram of the temperature-time evolution curve of the target formation in the well.

[0036] Figure 5 This is a cross-sectional schematic diagram of the final morphology of the ternary composite plug.

[0037] Figure 6 This is a schematic diagram of the three-dimensional relationship between the exothermic reaction rate of H2O2 / Na2SO3 and temperature and concentration.

[0038] Figure 7 This is a timeline diagram of the entire construction process of this invention.

[0039] Figure labels: 1-Oxidizing fluid storage tank, 2-Reducing fluid storage tank, 3-Alloy suspension storage tank, 4-High-pressure injection pump set, 5-Coaxial dual-fluid continuous tubing, 6-Wellhead blowout preventer, 7-Casing, 8-Target plugging section, 9-Downhole static mixer, 10-Micro-annulus / micro-fracture area to be repaired, 11-Flowback line, 12-Outer pipe, 13-Inner pipe, 14-Annulus channel, 15-Inner pipe channel, 16-Suspension channel, 17-Static mixing spiral blade, 18-Delayed mixing chamber, 19-Soluble diaphragm, 20-Outlet nozzle, 21-Bi-Sn-X alloy core, 22-Transition layer, 23-Inner organic film, 24-Outer reinforcing film, 25-Hydrophilic groups on film surface. 26-Rapid heating section curve, 27-Peak plateau section curve, 28-Late heat of fusion absorption plateau curve, 29-Slow cooling section curve, 30-Late heat of solidification release plateau curve. 31-Casing inner wall; 32-Bi-Sn-X metallic solidified phase; 33-Metal-inorganic transition phase; 34-Ca(OH)2 / Mg(OH)2 hydration expansion phase; 35-Original cement sheath; 36-Formation rock; 37-Filled micro-annulus; 38-Filled micro-fracture; 39-Compressive stress zone generated by solidification expansion of the metallic phase; 40-Basic system surface; 41-Adding thickener to delay system surface; 42-Adding catalyst to accelerate system surface; 43-Pre-flushing stage; 44-Alloy suspension injection stage; 45-Dual-liquid heat source injection and downhole mixing stage; 46-Pump shutdown and well shut-in reaction stage; 47-Temperature peak and alloy melting stage; 48-Alloy solidification and expansion stage; 49-Flowback and seal verification stage. Detailed Implementation

[0040] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0041] To address the problems in the background art, this invention provides a Bi-Sn-X alloy sealing composite medium comprising an oxidizing solution, a reducing solution, a Bi-Sn-X alloy composite material, and a slow-release expansion heat source material. The oxidizing solution is prepared by weighing and mixing H₂O₂, benzotriazole corrosion inhibitor, HPAM thickener, sodium pyrophosphate stabilizer, and deionized water according to a specified ratio. The reducing solution is prepared by weighing and mixing Na₂SO₃, ATMP scale inhibitor, pH buffer, EDTA-Na₄ chelating agent, and deionized water according to a specified ratio.

[0042] Bi-Sn-X alloy composite material consists of a Bi-Sn-X alloy core as the core body, coated from the inside out with a metal oxide layer, an organic film, and a reinforcing film. X is selected from one or more of In, Ag, Cu, Zn, and Sb. The melting point of the Bi-Sn-X alloy composite material is 80℃~160℃. The melting point of the Bi-Sn-X alloy core can be flexibly adjusted using a ternary phase diagram to meet the target bottom-hole temperature. Generally, the alloy melting point is designed to be slightly higher than the bottom-hole static temperature and lower than the downhole reaction peak temperature, so that the alloy remains solid during installation and settling, melting after the exothermic reaction raises the temperature. For example, a Bi-Sn-Sb system can be used to increase the melting point for high-temperature wells, while a Bi-Sn-In system can be used to lower the melting point for lower-temperature wells. The Bi-Sn-X alloy core can be self-made or purchased according to usage requirements; this invention does not limit the source of this raw material. Figure 3 This is a schematic diagram of the microstructure of the coating film on the surface of a Bi-Sn-X alloy core. The Bi-Sn-X alloy core, such as Bi... 51 Sn 32 In 17 The melting point is 80℃~160℃, with a solidification expansion of 0.1-3.3%. The transition layer (metal oxide 5nm~50nm) is formed by natural oxidation or anodizing, preventing the outward diffusion of alloy atoms. The inner organic film is specifically polyethylene wax or paraffin wax, with a thickness of 10μm~15μm. It has a melting point of 60℃~80℃ and melts layer by layer at 95℃~145℃, delaying direct contact between the alloy and H2O2, achieving the first layer of time-series protection; after melting, it acts as a flow lubricant. The outer reinforcing film is specifically epoxy resin E-51 or PLA, with a thickness of 15μm~25μm. It provides mechanical strength to prevent particle breakage during pumping; the outer reinforcing film contains hydrophilic groups, is compatible with the xanthan gum carrier liquid, and is stable in suspension. The hydrophilic groups (-OH, -COOH, etc.) on the film surface ensure that the particles are dispersed and do not agglomerate in the xanthan gum aqueous solution, and it is resistant to salt concentrations of 45000mg / L.

[0043] The main reaction pathway of this invention (near-zero gas-producing redox reaction):

[0044]

[0045]

[0046] Taking H2O2 and Na2SO3 as examples, the standard reaction enthalpy change ΔH≈-340kJ / mol (based on H2O2), and the heat release density per unit mass is about 10MJ / kg~12MJ / kg (based on the total mass of H2O2 and Na2SO3 reactants, it is 2.5MJ / kg~3.5MJ / kg). It can raise the temperature of the target layer from the initial 60℃~90℃ to 130℃~200℃ and maintain it for 30min~180min with a reactant mass of 50kg~500kg.

[0047] Theoretical model of temperature field: The temperature rise process of the target section downhole can be described by the following energy conservation equation: ; Where ρ is the system density (kg / m³), and c p is the specific heat capacity (J / (kg·K)), and k is the effective thermal conductivity (W / (m·K)). This is the exothermic source term for the chemical reaction (W / m³). The heat loss to the formation and casing (W / m³). t represents the latent heat absorption term of the alloy core melting process (W / m³), T is the temperature (K), and t is the time (s). This is the gradient operator.

[0048] Reaction exothermic source term Second-order dynamics are used to describe the process: ; Where k0 is the pre-exponential factor, E a The apparent activation energy is given (typically 40 kJ / mol to 60 kJ / mol), R is the universal gas constant, 8.314 J / (mol·K), and T is the temperature, C. H2O2 The concentration of hydrogen peroxide. ΔH represents the concentration of sulfite ions, and ΔH represents the molar heat of reaction.

[0049] Alloy latent heat of melting : ; Where, ρ m The density of the alloy (typical Bi-Sn eutectic is about 8740 kg / m³). The latent heat of fusion is approximately 44.8 kJ / kg for Bi-Sn eutectic. The fraction of liquid phase is 0~1, and t is time.

[0050] Solidification expansion model: Volume expansion rate during solidification of Bi-Sn-X alloy Related to components: ; Among them, V s V is the volume of the alloy after solidification. l This is the volume of the alloy when it is melted into a liquid state.

[0051] For Bi-Sn eutectic systems with Bi content of 50wt%~58wt%, ε v It is typically in the range of 0.1% to 0.5%; by adding elements such as In and Sb, ε can be increased. v Adjust to 0.5%~3.3% to create an active sealing pressure σ between the surrounding rock and the casing. seal Active sealing pressure σ seal The calculation formula is: ; in, This is the effective elastic modulus of the alloy (approximately 30 GPa to 50 GPa). The geometric constraint factor is 0.01 to 0.1.

[0052] This invention establishes a wellbore repair system that solves four major bottleneck problems in wellbore repair: gas production pores, premature reaction corrosion, difficulty in entering micro-cracks, and poor durability. This is achieved through a chain of three independent surface tanks, three-channel coaxial conveying, downhole static mixing, soluble diaphragm delay, three-layer coated alloy sequential melting, zero-porosity four-stage expansion composite sealing, and backflow.

[0053] like Figure 1 and Figure 2 As shown, the wellbore repair system used in this invention includes: a coaxial dual-fluid continuous tubing 5, which is installed inside the casing 7 of the wellbore and extends along the inside of the casing 7 to above the target sealing section 8 downhole, specifically at a distance of 1m to 10m above the target sealing section 8; the coaxial dual-fluid continuous tubing 5 is formed by coaxially sleeved outer tube 12 and inner tube 13, an annular channel 14 is formed between the inner wall of the outer tube 12 and the outer wall of the inner tube 13, an inner tube channel 15 is formed inside the inner tube 13, and a suspension channel 16 is provided on one side of the outer tube 12 wall; a wellhead blowout preventer 6 is provided above the coaxial dual-fluid continuous tubing 5; the target sealing section 8 mentioned in this invention is located in the section that needs to be repaired, such as the well depth of 2855m to 2865m.

[0054] Oxidizing liquid storage tank 1, which is arranged on the ground and used for storing oxidizing liquid, the outlet of the oxidizing liquid storage tank 1 is communicated with the first inlet of the high-pressure injection pump unit 4 through the first pipeline, and the first outlet of the high-pressure injection pump unit 4 is communicated with the annulus channel 14 through the wellhead blowout preventer 6; reducing liquid storage tank 2, which is arranged on the ground and used for storing mixed liquid; the outlet of the reducing liquid storage tank 2 is communicated with the second inlet of the high-pressure injection pump unit 4 through the second pipeline, and the second outlet of the high-pressure injection pump unit 4 is communicated with the inner pipe channel 15 through the wellhead blowout preventer 6; alloy suspension storage tank 3, which is arranged on the ground and used for storing alloy suspension; the outlet of the alloy suspension storage tank 3 is connected with the third inlet of the high-pressure injection pump unit 4 through the third pipeline, and the third outlet of the high-pressure injection pump unit 4 is communicated with the suspension channel 16 through the wellhead blowout preventer 6. In the present invention, an anchor-type low-shear agitator (Jiangsu Zhongyi, model MJB-100, rotating speed 150-300rpm) is arranged in the alloy suspension storage tank 3, which continuously agitates before and during transportation to prevent the Bi-Sn-X alloy composite material (Stokes sedimentation velocity is about 0.02m / s) with relatively high specific gravity from settling, keeps the viscosity of the liquid at 60-80mPa·s, and ensures the displacement of 0.15-0.20m 3 / min for stable transportation. In addition, a paddle agitator (rotating speed 100-200rpm, agitating for 10-15min) is arranged in the reducing liquid storage tank 2, so that the slow-release expansion heat source material is uniformly dispersed in the reducing liquid, and high shear (<500s -1 ) is avoided to damage the microcapsule shell layer. Samples are taken to detect the dispersion uniformity before transportation, and the standing delamination rate after 30min <5% is qualified.

[0055] The downhole static mixer 9 is detachably connected to the bottom of the coaxial dual-liquid continuous tubing 5. Furthermore, the downhole static mixer 9 is threadedly connected to the bottom of the coaxial dual-liquid continuous tubing 5, specifically located directly above or slightly below the target sealing layer 8, depending on the construction requirements; the invention does not impose a specific location limitation. The downhole static mixer 9 contains, from top to bottom, static mixing spiral blades 17, a delayed mixing chamber 18, a soluble diaphragm 19, and an outlet nozzle 20; the initial mixing of the oxidizing and reducing liquids occurs within the downhole static mixer 9. Further, 2-3 static mixing spiral blades 17 are fixed at the junction of the annular channel 14 and the outlet of the inner tube 15. The oxidizing and reducing liquids undergo initial cutting and deflection here, achieving efficient mixing without power. Then, a delayed mixing chamber 18 is located below the static mixing spiral blades 17, its volume providing residence time for the reaction liquid, thus slowing down the reaction rate regulated by the thickener (HPAM / xanthan gum), and controlling the peak temperature arrival time. The soluble diaphragm 19 is a PVA or PLA film with controllable thickness. It is insoluble at low temperatures and initial pH, maintaining temporary isolation of the oxidation / reduction solution upon entry into the chamber. It dissolves when the temperature rises above 80°C or the pH changes, achieving controllable delayed triggering and preventing premature reaction that could clog the oil pipe. Finally, the alloy core melts into a liquid state and is ejected from the outlet nozzle 20, which is a conical converging nozzle located at the bottom. Specifically, the PVA film is purchased from Kuraray Ecomate PVA Film, model E-105 or M-2050, with a thickness of 80±10μm, tensile strength ≥35MPa, and elongation at break ≥300%. The polylactic acid (PLA) film is purchased from NatureWorks Ingeo Film 4032D, with a thickness of 100±15μm, a glass transition temperature of 55-60°C, and a melting point of 155-160°C. In this invention, the soluble diaphragm 19 is a PVA film of model E-105.

[0056] The runoff pipeline 11 has one end located inside the wellbore below the target sealing section 8, and the other end extends upward along the inside of the casing 7, connecting to the surface treatment assembly via the wellhead blowout preventer 6. The surface treatment assembly is used to treat the runoff Na2SO4 or NaHSO4 brine byproducts, with a pH of approximately 7.8.

[0057] The high-pressure injection pump set 4 of this invention is a triple pump or a set of pumps, including three independent inlets (first inlet, second inlet, and third inlet) and three independent outlets (first outlet, second outlet, and third outlet), each with controllable discharge rate. Different liquids are delivered according to construction requirements. The wellhead blowout preventer 6 of this invention is located above the coaxial dual-liquid continuous tubing 5, i.e., at the top of the casing 7, and is used to seal the wellhead. The wellhead blowout preventer 6 has a dual-liquid rotary joint inside, corresponding to the annular channel 14, the inner tube channel 15, and the suspension channel 16, respectively, to prevent high-pressure blowouts.

[0058] from Figure 1 As can be seen, during the repair and plugging of the target wellbore, the casing 7 provides a channel for downhole tools and fluids. The required oxidant is stored in the oxidant storage tank 1. The reducing agent and slow-release expansion heat raw materials are premixed on the surface and stored in the reducing agent storage tank 2. The alloy suspension is stored in the alloy suspension storage tank 3. The alloy suspension is pumped in first, and then the oxidant and the mixture are pressurized by the high-pressure injection pump group 4 and injected through the coaxial dual-liquid continuous tubing 5. They are mixed at the downhole static mixer 9, where an exothermic reaction occurs. The alloy core melts into a liquid state and, driven by downhole pressure difference and gravity, seeps from the target plugging section 8 into the area of ​​the wellbore to be repaired, such as the micro-annulus / micro-fracture area 10 to be repaired. After cooling, a plugging layer is formed, thereby effectively plugging the target plugging section 8. After the operation is completed, the remaining liquid in the micro-annulus / micro-fracture area 10 to be repaired or the target plugging section 8 is discharged to the surface through the return pipeline 11. The function of the wellhead blowout preventer 6 is to close the wellhead during operation to prevent blowout accidents.

[0059] This invention employs a coaxial dual-liquid continuous tubing 5 to transport the oxidizing liquid and reducing liquid (containing a slow-release expansion heat source material) to the target downhole formation. Specifically, before transporting the oxidizing liquid, reducing liquid, and slow-release expansion heat source material, an alloy suspension is first transported to the target sealing formation 8 through the suspension channel 16. After the transport is completed, the oxidizing liquid is transported through the annular channel 14, and the mixed liquid (slow-release expansion heat source material and reducing liquid) is transported through the inner tube channel 15. The oxidizing liquid and reducing liquid are mixed and reacted in the downhole static mixer 9. During the mixing process, an oxidation-reduction reaction occurs, releasing heat, and the slow-release expansion heat source material also releases heat, causing the Bi-Sn-X alloy core to melt and form a Bi-Sn-X alloy molten liquid. Driven by the downhole pressure differential and gravity, the Bi-Sn-X alloy molten liquid seeps into microfractures, microannular spaces, or void channels, and after solidification and expansion, forms a composite sealing body, completing the sealing. Bi-Sn-X alloy composite materials achieve sequential control of the reaction process—first exothermic, then metal melting, and finally solidification expansion—through delayed dissolution of the coating film.

[0060] This invention employs a coaxial dual-liquid continuous tubing 5 to transport various liquids. An annular channel 14 is used to transport the oxidizing liquid, the inner tubing channel 15 is used to transport the mixed liquid, and the suspension channel 16 is used to transport the alloy suspension. These three channels remain isolated from each other before reaching the target plugging section 8 downhole. They are mixed in a downhole static mixer 9, ultimately melting into a liquid alloy core which is injected into the target plugging section 8. Using pressure differential and gravity, it penetrates into the micro-annular / micro-fracture region 10 to be repaired. After the temperature drops, the alloy solidifies, forming a plugging body. A cross-sectional schematic diagram of the final morphology of the ternary composite plugging body is shown below. Figure 5As shown, from the inner wall of the casing 7 to the original cement ring 35, the sealing body sequence is as follows: Bi-Sn-X metallic solidified phase 32 (dense region), metal-inorganic transition phase 33, and Ca(OH)2 / Mg(OH)2 hydration expansion phase 34, forming a multi-level sealing structure of metallic core and inorganic shell. After the alloy core solidifies, the Bi-Sn-X metallic solidified phase 32, when the molten Bi-Sn-X alloy penetrates into the microcracks, reacts with the OH- produced by the hydration of CaO / MgO. - An interfacial reaction occurs, forming a small amount of Bi-Sn-X(OH). x The transition layer, namely the metal-inorganic transition phase 33, and the CaO and / or MgO microcapsule sustained-release heat source are formed into the hydration expansion phase 34 through a hydration reaction. The reaction mechanism of the CaO microcapsule sustained-release heat source is: CaO + H2O → Ca(OH)2. This reaction process is accompanied by exothermic reaction and volume expansion. Under constrained conditions, the apparent volume expansion is 1.5~2.5%.

[0061] The reaction mechanism of the MgO microcapsule sustained-release pyrogen is: MgO + H2O → Mg(OH)2. This reaction process is accompanied by exothermic reaction and volume expansion. Under constrained conditions, the apparent volume expansion is 1.0~2.0%.

[0062] Figure 4 The diagram shows the temperature-time evolution curve of the target formation in the well. The horizontal axis represents time t (unit: min), and the vertical axis represents temperature T (unit: ℃). The curves represent the rapid heating segment 26 (0 min ~ 15 min), the peak plateau segment 27 (15 min ~ 120 min), the latent heat absorption plateau 28 (near the alloy melting point, 80℃ ~ 160℃), the slow cooling segment 29 (120 min ~ 240 min), and the solidification latent heat release plateau 30. Figure 6 This is a schematic diagram of the three-dimensional relationship between the exothermic reaction rate of H2O2 / Na2SO3 and temperature and concentration. The X-axis represents temperature T (°C), the Y-axis represents the initial concentration of H2O2 C0 (mol / L), and the Z-axis represents the exothermic reaction rate. (Unit: W / L), the curved surfaces are the basic system 40, the thickener-added retarded system 41, and the catalyst-added accelerated system 42.

[0063] It should be noted that, Figure 4 and Figure 6 The curves in the figure are obtained through numerical simulation using MATLAB based on the energy conservation equation and the second-order dynamic model. The parameters used in the simulation are from the measured data of Example 1 and Example 2. Figure 4 The target formation energy conservation model can be used for simulation. The model includes exothermic terms of redox reaction, slow heat release terms of CaO / MgO hydration, latent heat absorption terms of alloy melting, and heat dissipation terms to casing, cement sheath and formation.

[0064] ; Where T is the temperature of the target layer, t is time, and ρ eff For equivalent density, c eff For the equivalent specific heat capacity, k eff q is the equivalent thermal conductivity; redox The exothermic term is generated by the reaction of hydrogen peroxide with sulfite, q hyd This is a term representing the slow-release heat generated by the hydration of CaO and / or MgO. For the heat loss term of casing, cement sheath and formation, q melt This is the latent heat absorption term during the melting process of Bi-Sn-X alloy.

[0065] The heat dissipation loss term can be simplified as follows: ; Where h is the equivalent heat transfer coefficient, A is the heat transfer area, and T is the initial temperature at the bottom of the well or the temperature of the surrounding formation.

[0066] ; Where, m m For alloy quality, L m The latent heat of the alloy's melting point. This represents the liquid phase fraction of the alloy. It can be processed according to the linear change of temperature between the solidus temperature and the liquidus temperature.

[0067] Figure 6 The reaction kinetics of hydrogen peroxide and sulfite can be simulated using a second-order kinetic model. The exothermic reaction rate is related to temperature, hydrogen peroxide concentration, and sulfite concentration. Taking the reaction of hydrogen peroxide and sulfite as an example, the reaction rate can be represented by a second-order kinetic model: ; Where r is the reaction rate, k0 is the pre-exponential factor, and E a Let R be the apparent activation energy, R be the gas constant, T be the reaction temperature, and C be the temperature. H2O2 The concentration of hydrogen peroxide. This represents the concentration of sulfite ions.

[0068] ; Where, ΔH redox This represents the enthalpy change of a redox reaction. Since this reaction is exothermic, the exothermic heat can be written as -ΔH when it is positive. redox ·r.

[0069] In drawing Figure 6 At this time, hydrogen peroxide and sulfite can be treated at approximately equimolar concentrations, that is: ; The heat release rate can then be simplified to: ; in, This represents the initial concentration of the reactants. This formula can be used to generate... Figure 6 A three-dimensional surface relating temperature, concentration, and exothermic rate.

[0070] Figure 7 This is a timeline diagram of the entire construction process of this invention. The specific time consumption is dynamically adjusted according to the well depth, discharge rate, and reaction time. The horizontal axis is time t (unit: h), and the vertical axis is the construction stage, which is described as follows: including (1) pre-flushing stage 43, the time is from 0h to 1h, pumping in pre-flushing fluid to remove Ca 2+ Ba 2+ (2) Alloy suspension injection stage 44, time from the 1st to the 2nd hour, Bi-Sn-X alloy composite material is deposited in the target sealing layer 8 under the carrying of xanthan gum. Preferably, the alloy core is densely packed and bridged by granular 60wt%~80wt%, rod 10wt%~30wt%, and the remainder fibrous gradation, which can better repair the micro-annulus / micro-fracture area 10. (3) Dual liquid heat source injection and downhole mixing stage 45, time from the 2nd to the 3rd hour, the oxidizing liquid enters the annulus channel 14, and the mixing liquid enters the inner tube channel 15 and is mixed at the downhole static mixer 9. Taking H2O2 and Na2SO3 as an example, there is no N2 or H2 gas after the reaction, and the gas production is close to zero, avoiding pores. The reducing agent is slightly in excess at a molar ratio of 1.02-1.10:1 to ensure that the residual H2O2 is <50mg / L and does not corrode the alloy and casing. The pH buffer controls the pH of the system to be 6-9, which is near neutral and weakly alkaline. (4) Pump shut-off and well shut-in reaction stage 46, the time is from the 3rd to the 6th hour. After the soluble diaphragm 19 dissolves, the reaction continues to release heat in the delayed mixing chamber 18. The temperature rises from 78℃ to 145℃~192℃, and the peak value is maintained for 90min~150min. Slow-release expansion heat source material (taking calcium oxide slow-release expansion heat source material as an example), CaO+H2O→Ca(OH)2 continuously releases heat for 30min and is kept warm. (5) Temperature peak and alloy melting stage 47, the time is from the 3.5th to the 5th hour, combined with Figures 3-4Through rapid heating 26, it reaches the latent heat plateau 28 (alloy endothermic), and then the peak plateau 27. At this time, the inner organic film 23 and the outer reinforcing film 24 dissolve, and the alloy core 21 melts into a liquid state with excellent fluidity. Under gravity and expansion pressure, it penetrates into micro-annular spaces and micro-cracks (width 50μm~300μm can enter). (6) Alloy solidification and expansion stage 48, time is from the 5th to the 8th hour. After the peak plateau 27 ends, it slowly cools down 29 and reaches the solidification exothermic plateau 30. The alloy solidification expansion is 0.8%~1.2%, generating σ=E·εv·η≈21MPa contact stress (active interlocking). At the same time, the hydration line expansion of Ca(OH)2 and / or Mg(OH)2 is 1.5%~2.5%, forming a metal-inorganic composite plug, such as Figure 5 As shown. Density > 99%, withstands 50 MPa pressure difference. (7) Backflow and sealing stage 49, time is from the 8th to the 12th hour. At this time, brine is backflowed through backflow pipeline 11, pressure is tested at 30 MPa and stabilized for 30 minutes with a pressure drop < 0.2 MPa.

[0071] In the following examples, partially hydrolyzed polyacrylamide, abbreviated as HPAM, was purchased from Beijing Hengju Company, with a molecular weight of 12 million and model number HPAM-1200; xanthan gum was purchased from Shandong Fufeng, with a molecular weight >2 million and food grade. The molecular weight of polyethylene wax was approximately 3000. CaO powder was purchased from Sinopharm Chemical Reagent Co., Ltd. (Shanghai), analytical grade CaO, with a particle size D50 = 3-5 μm and model number 10005961. MgO powder was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., model number A119654, light MgO, 99.9%. Polyvinyl alcohol (PVA) was purchased from Kuraray, specification PVA-1788, with a degree of alcoholysis of 88% and a degree of polymerization of 1700. Polylactic acid (PLA) was purchased from NatureWorks Ingeo 4032D, with a molecular weight of 150,000. Epoxy resin E-51 was purchased from Nantong Xingchen Synthetic Materials, and curing agent T-31 was purchased from Guangzhou Kafen Chemical. The Bi, Sn, and In used in the following examples are all 4N grade.

[0072] Example 1: Repair of micro-annulus in casing-cement sheath of a high water-cut oil well Operating conditions: An oil well in an oilfield in western China, at a depth of 3200m, with the target repair zone located at a depth of 2850m~2870m. The casing specifications are Φ139.7mm×7.72mm. The bottom hole static temperature is 78℃, the bottom hole pressure is 28MPa, the formation water salinity is 45000mg / L, and the Ca content is... 2+ Content 1200 mg / L, Ba 2+The content is 80 mg / L, containing trace amounts of H2S (approximately 50 mg / L). Sonic variable density logging (CBL / VDL) shows that there are micro-annulus with a width of 80 μm to 300 μm in the casing-cement sheath section between 2855m and 2865m, causing water channeling between upper and lower layers.

[0073] This embodiment provides a Bi-Sn-X alloy sealing composite medium, which is composed of a reducing liquid, an oxidizing liquid, a Bi-Sn-X alloy composite material, and a slow-release expansion heat source material.

[0074] (1) The total mass of the oxidizing solution is 200 kg, which consists of the following components: 70 kg H2O2; 1.0 kg benzotriazole corrosion inhibitor; 1.2 kg HPAM thickener; 0.4 kg sodium pyrophosphate stabilizer; and 127.4 kg deionized water. In this embodiment, the H2O2 is 35 wt% industrial grade, that is, the mass of pure H2O2 is 24.5 kg.

[0075] (2) The total mass of the reducing solution is 220 kg, which is composed of the following components: 90 kg Na2SO3 (industrial grade ≥97%): (approximately 714 mol, n(SO3) 2- The mixture consisted of 1.5 kg ATMP scale inhibitor, 3 kg pH buffer, 0.5 kg EDTA-Na4 chelating agent, and 125 kg deionized water. The pH buffer was composed of 1.2 kg Na2HPO4 and 1.8 kg NaH2PO4. In this embodiment, the initial pH of the reducing solution was adjusted to 7.5 using the pH buffer.

[0076] (3) The mass of the Bi-Sn-In alloy composite material is 92 kg; wherein, the mass of the Bi-Sn-In alloy core is 90 kg, the particle size is 100 μm to 500 μm, and the melting point is 95 °C; the Bi-Sn-In alloy core is coated with a 10 μm polyethylene wax layer and a 15 μm epoxy resin layer from the inside to the outside; in order to facilitate subsequent transportation, in this embodiment, the Bi-Sn-In alloy composite material is prepared into an alloy suspension before transportation.

[0077] The total mass of the alloy suspension is 152 kg. The preparation steps of the alloy suspension are as follows: Step 1: Bi, Sn, and In were mixed in a ratio of Bi 50wt%, Sn 30wt%, and In 20wt% under a high-purity argon atmosphere (Ar purity ≥ 99.99%) at a flow rate of 5 L / min, and electromagnetically stirred at 350±5℃ for 2 hours to form a homogeneous alloy liquid with a superheat of 60℃. Then, a gas atomization process was performed using a Changsha Tianjiu LB-500E gas atomizer with the following parameters: quartz crucible orifice diameter 6 mm, atomizing gas Ar, atomization pressure 4.5 MPa, gas-liquid mass ratio 3.5:1, and nozzle distance from the receiving tank 1.2 m. The alloy liquid was atomized at a flow rate of 0.8 kg / min to prepare granular Bi-Sn-In alloy cores. These cores were then screened using a vibrating sieve to obtain the 100μm~500μm end, with a yield of 85%, for later use.

[0078] Step 2: Mix 8 kg of polyethylene wax and 92 kg of toluene evenly to obtain a polyethylene wax / toluene solution with a mass concentration of 8%. Completely immerse 90 kg of granular Bi-Sn-In alloy cores with a particle size of 100 μm to 500 μm in the 8% polyethylene wax / toluene solution at 80℃ for 10 minutes. After immersion and drying, check the film thickness. If the thickness does not meet the requirements, repeat the immersion and drying process until the polyethylene wax layer reaches the target thickness of 10 μm, finally obtaining an alloy material containing polyethylene wax.

[0079] Step 3: Mix 10 kg of E-51 and 2.5 kg of T-31 to form a mixed solution. Then, place the alloy material containing polyethylene wax prepared in Step 2 into the above mixed solution and cure it at 60°C for 2 hours. After removing and drying, check the film thickness. If the thickness does not meet the requirements, repeat the impregnation and drying process until the epoxy resin layer reaches the target thickness of 15 μm to obtain the epoxy resin-containing alloy material. The product obtained in this step is the Bi-Sn-In alloy composite material.

[0080] Step 4: Add 92 kg of the Bi-Sn-X alloy composite material prepared in Step 3 to 60 kg of xanthan gum aqueous solution with a mass concentration of 5%, and mix evenly to obtain 152 kg of alloy suspension.

[0081] (4) Slow-release expansion heat source material: 30 kg of CaO microcapsule powder. The CaO microcapsule powder needs to be premixed with the reducing solution before subsequent use. The preparation method of CaO microcapsule powder is as follows: 2.5 kg of PVA and 47.5 kg of deionized water at 90°C were mixed and mechanically stirred at 90°C and 400 rpm for 2 hours to dissolve the PVA. After cooling to room temperature, a 5% PVA aqueous solution with a viscosity of approximately 45 mPa·s was obtained.

[0082] 10 kg of CaO powder was dispersed in 50 L of 5% PVA aqueous solution and ultrasonically dispersed for 10 min. Then, it was sheared at 8000 r / min for 15 min using an IKA T25 high-shear dispersing emulsifier. After shearing, 1.35 kg of 37% formaldehyde was added, and the pH of the system was adjusted to 2.5 with 1 mol / L hydrochloric acid. The reaction was then carried out at 60℃ and 350 rpm for 4 h. After the reaction, the PVA hydroxyl groups acetalized with formaldehyde to form a shell, which was then spray-dried using a Wuxi Dongteng L-5 centrifugal spray tower with an inlet air temperature of 120℃, an outlet air temperature of 60℃, a centrifugal disc speed of 18000 rpm, and a peristaltic pump feed rate of 15 mL / min. CaO microcapsules with a particle size of 50 μm to 150 μm were obtained. The PVA shell thickness of the CaO microcapsules was 5-8 μm, and the dissolution rate was <5% after 2 h.

[0083] This embodiment also provides a construction method, the operation steps of which are as follows: Step 1, Pre-flushing step: Pump 5m into the target layer. 3 The pre-rinse solution contains 0.5 wt% EDTA and 0.3 wt% aminotrimethylenephosphonic acid (ATMP), with a discharge rate of 0.3 m³. 3 / min. This step is to remove oil and calcium from the target layer. 2+ Ba 2+ Ions are used to prevent the formation of BaSO4 and CaSO4 scale in subsequent reactions.

[0084] Step Two (Alloy Suspension Injection): Pump 150 kg of alloy suspension into the well section at a depth of 2855 m to 2865 m through suspension channel 16 (outer annulus) of the coaxial continuous tubing, at a displacement of 0.15 m³ / min. 3 / min.

[0085] Step 3 (Dual-liquid heat source injection and downhole mixing): The oxidizing fluid is simultaneously pumped in through the outer annular channel and the reducing fluid through the inner pipe channel to the downhole static mixer (located at 2860 m) for mixing and reaction. The oxidizing fluid discharge rate is 0.10 m³ / h. 3 / min, the displacement of the reducing solution is 0.11m 3 / min, controlling the volume ratio of oxidizing solution to reducing solution to approximately 1:1.1.

[0086] Step 4 (Pump Shutdown and Well Shutdown Reaction): After pumping is completed, the wellhead blowout preventer is shut off, allowing the reaction system to release heat in a closed loop within the target formation. The downhole temperature was monitored to rise from 78°C to a peak of 145°C (the peak temperature was reached at approximately 3.5 hours), and the peak temperature was maintained for approximately 90 minutes.

[0087] Step 5 (Alloy melting and flow filling): Within the temperature range of 95℃ to 145℃, the organic film on the surface of the alloy core melts / dissolves layer by layer, and the alloy core melts into a liquid state, which then penetrates into the micro-annulus (80μm~300μm width) under the drive of downhole pressure differential and gravity.

[0088] Step Six (Alloy Solidification and Expansion): After the exothermic reaction ends, the temperature slowly decreases. Combined with the hydration of CaO microcapsule powder, the heat is released gradually for approximately 30 minutes, allowing the alloy sufficient time to remain in the liquid state. When the temperature drops below 95℃, the alloy solidifies, expanding in volume by approximately 1.2%, generating a local contact stress of approximately 21 MPa at the interface between the sleeve and the cement ring (equivalent to a macroscopic sealing pressure of approximately 20 MPa~30 MPa). The formula for calculating the local contact stress in this step is: σ = E eff ˙ε v ˙η constraint =35GPa×0.012×0.05=21MPa.

[0089] Among them, E eff The effective elastic modulus, valued at 35 GPa based on Bi-Sn alloy literature; ε v The yield strain is 0.012; η constraint The constraint factor is obtained through finite element simulation and has a value of 0.05.

[0090] Step Seven (Flowback and Sealing Verification): Open the well and flow back approximately 3.5m of Na2SO4 brine byproducts. 3 (Including unreacted residual liquid), the pH of the backflow solution was measured to be 7.8, and the residual H2O2 concentration was <50mg / L (meeting environmental emission requirements); a water injection pressure test was conducted, with a pressure stabilization of 30MPa for 30min and a pressure drop of <0.2MPa, indicating that the seal was qualified.

[0091] The Bi-Sn-X alloy sealing composite medium prepared in this embodiment was used to repair the oil well. After repair, water channeling in the well section was eliminated, and the water cut decreased from 88% before the operation to 32%, resulting in a daily oil production increase of 4.5m³. 3 / d, the total cost of single-well repair is approximately RMB 180,000 (materials + operations), which is significantly lower than the conventional cement extrusion process (approximately RMB 350,000, with a success rate of less than 40%). The repaired body remained perfectly sealed after 6 months of well temperature-well pressure cycle testing.

[0092] Example 2: Permanent sealing of an abandoned high-sulfur gas well Background: An abandoned high-sulfur gas well in Southwest China, 4500m deep, with the original producing layer at 4200m-4280m. H2S content is 12 vol%, CO2 content is 6 vol%, bottom hole temperature is 138℃, and bottom hole pressure is 62 MPa. The well needs to be sealed according to national standards for a 1000-year long-term seal to prevent acid gas from rising into the freshwater layer. Testing of the existing cement plug revealed a micro-crack zone at 4220m, with a width of 50μm-200μm and a longitudinal extension of approximately 12m.

[0093] This embodiment provides a Bi-Sn-X alloy sealing composite medium, which is composed of a reducing liquid, an oxidizing liquid, a Bi-Sn-X alloy composite material, and a slow-release expansion heat source material.

[0094] (1) The total mass of the oxidizing liquid is 600 kg, which is composed of the following components: 240 kg H2O2; 6.0 kg N-benzyl-2-heptyl-1-hydroxyethylimidazoline chloride; 4.5 kg xanthan gum thickener; 1.5 kg sodium stannate stabilizer; 348 kg deionized water.

[0095] In this embodiment, the H2O2 is 50wt% industrial grade, that is, the mass of pure H2O2 is 120kg, approximately 3530mol.

[0096] (2) The total mass of the reducing solution is 700 kg, which is composed of the following components: Na2S2O5 (sodium metabisulfite, industrial grade): 350 kg (the number of moles is about 1842 mol, calculated based on 1 mol Na2S2O5 eliminating 2 mol H2O2, n(H2O2):n(Na2S2O5)≈1.92:1, the actual reducing agent is slightly in excess by about 5%); 5.0 kg ethylenediaminetetramethylenephosphonic acid (EDTMP) scale inhibitor; 12 kg pH buffer; 3.0 kg EDTA-Na4 chelating agent; 330 kg deionized water.

[0097] The pH buffer consists of 4.8 kg of boric acid and 7.2 kg of borax. In this embodiment, the initial pH of the reducing solution is adjusted to 8.2 using the pH buffer.

[0098] (3) The mass of the Bi-Sn-Sb alloy composite material is 350 kg; among which, the solidification expansion rate of the Bi-Sn-Sb alloy core is about 0.8%, and the resistance to H2S is excellent; considering that the bottom temperature of 138℃ is close to the melting point of the alloy, this embodiment selects the Bi-Sn-Sb system with a melting point of 155℃~160℃ (Bi 52wt%, Sn 38wt%, Sb 10wt%) to ensure that the alloy core remains solid at the bottom temperature and melts when the reaction temperature is raised to 175℃~195℃.

[0099] The Bi-Sn-Sb alloy core is composed of the following components by mass percentage: 60% granular Bi-Sn-Sb alloy core with a particle size of 200μm~800μm, 30% rod-shaped Bi-Sn-Sb alloy core with a size of 1mm×5mm, and 10% fibrous Bi-Sn-Sb alloy core with a diameter of 200μm and a length of 3mm (used for bridging large cracks); the Bi-Sn-Sb alloy core is coated with a 15μm paraffin layer and a 25μm PLA layer from the inside to the outside.

[0100] To facilitate subsequent transportation, in this embodiment, the Bi-Sn-Sb alloy composite material is prepared into an alloy suspension before transportation. The total mass of the alloy suspension is 500 kg.

[0101] The preparation steps of the alloy suspension are as follows: Step 1: Preparation of Bi-Sn-Sb alloy core Step 1.1: Bi, Sn, and Sb are mixed in a ratio of Bi 52wt%, Sn 38wt%, and Sb 10wt%. Under a high-purity argon atmosphere (Ar purity ≥ 99.99%), with an argon flow rate of 5 L / min, the mixture is electromagnetically stirred and held at 350±5℃ for 2 hours to form a homogeneous alloy liquid with a superheat of 60℃. Then, a gas atomization process is performed using a Changsha Tianjiu LB-500E gas atomizer. The parameters are set as follows: quartz crucible orifice diameter 6 mm, atomizing gas Ar, atomization pressure 4.5 MPa, gas-liquid mass ratio 3.5:1, and nozzle distance from the receiving tank 1.2 m. The alloy liquid is atomized at a flow rate of 0.8 kg / min to prepare granular Bi-Sn-Sb alloy cores. These cores are then screened using a vibrating sieve to obtain the 100μm~500μm end, with a yield of 85%, for later use.

[0102] Step 1.2: Mix Bi, Sn, and Sb in a ratio of Bi 52wt%, Sn 38wt%, and Sb 10wt%, and stir electromagnetically at 350±5℃ for 2 hours under the protection of a high-purity argon atmosphere (Ar purity ≥ 99.99%) with an argon flow rate of 5L / min to form a homogeneous alloy liquid with a superheat of 60℃.

[0103] The molten alloy was poured into a graphite mold preheated to 150℃. This mold was a 36-cavity cylindrical array of 3mm × 60mm cylinders. After casting, the casting was rapidly solidified within the mold using air cooling. After solidification, the casting was demolded to obtain 3mm alloy rods. The 3mm alloy rods were cut using a Suzhou Hanya SYJ-400 precision cutting machine. The machine parameters were set as follows: spindle speed 1800rpm, feed rate 0.02mm / s. The rods were cut into short castings of L=9mm and 20mm. Burrs were removed, and the rods were ultrasonically cleaned with alcohol for 10 minutes. These short castings were then held at 80℃ before being fed into a tungsten carbide wire drawing die for multiple drawing passes, with a target diameter of 1mm. Specifically, the reduction rate per pass was 20%, the drawing speed was 0.5m / min, and paraffin oil was used as the lubricating and cooling medium during the drawing process. The obtained sample with a diameter of Φ1mm was cut into a length of 5mm to obtain a rod-shaped Bi-Sn-Sb alloy core.

[0104] Step 1.3: Mix Bi, Sn, and Sb in a ratio of Bi 52wt%, Sn 38wt%, and Sb 10wt%, and under the protection of a high-purity argon atmosphere (Ar purity ≥ 99.99%), with an argon flow rate of 5L / min, and keep at 380℃ for 2 hours with electromagnetic stirring to form a homogeneous alloy liquid.

[0105] The vacuum single-roll rapid quenching machine SK-300 manufactured by Beijing University of Science and Technology was used. The equipment parameters were as follows: copper roller diameter 250mm; crucible: quartz crucible with a 0.3mm × 10mm long-slit nozzle; crucible-copper roller distance 2mm; injection pressure: Ar pressurized 0.12MPa; copper roller linear velocity 12m / s (i.e., copper roller rotation speed 918rpm); cooling rate 10... 5 K / s yields continuous fiber tapes with a width of 0.5-1 mm and a thickness of 100-300 μm. The fiber tapes are then processed by a pelletizer (Jiangyin Jingcheng, cutter gap 0.05 mm), with a set length of 3 mm and a rotation speed of 300 rpm, to produce fibrous Bi-Sn-Sb alloy cores with a diameter of 200 μm and a length of 3 mm. Powder <1 mm is removed by sieving. Ar protection is maintained throughout the preparation process to prevent Sn oxidation; the surface roughness Ra of the copper roller is <0.2 μm; and the temperature of the collection box is <30℃.

[0106] Step 2: Weigh out the raw materials as follows: 60wt% granular Bi-Sn-Sb alloy cores with a particle size of 200μm~800μm, 30wt% rod-shaped Bi-Sn-Sb alloy cores with a size of 1mm×5mm, and 10wt% fibrous Bi-Sn-Sb alloy cores with a diameter of 200μm and a length of 3mm, for a total mass of 350kg. Place them in a Changzhou Zhiyang SYH-50 three-dimensional mixer and mix at 15rpm for 30min to obtain a mixture. Immerse the 350kg mixture completely in a 10% paraffin wax solution at 75℃ for 10min. Remove and dry, then check the film thickness. If the thickness does not meet the requirements, repeat the immersion and drying process until the paraffin wax layer reaches the target thickness of 15μm, finally obtaining an alloy material containing paraffin wax.

[0107] Step 3: Dissolve 15 kg of PLA in 200 L of dichloromethane to obtain a PLA solution. Place the paraffin-containing alloy material prepared in Step 2 into the above PLA solution, stir and coat for 30 min, remove and evaporate the solvent at room temperature, then dry at 40 °C for 6 h. After drying, measure the film thickness; if the thickness does not meet the requirements, repeat the impregnation and drying process until the PLA layer reaches the target thickness of 25 μm, obtaining an alloy material containing PLA. The product obtained in this step is the Bi-Sn-Sb alloy composite material.

[0108] Step 4: Add 350 kg of the Bi-Sn-Sb alloy composite material prepared in Step 3 to 150 kg of xanthan gum aqueous solution with a mass concentration of 8%, and mix evenly to obtain an alloy suspension with a total mass of 500 kg.

[0109] It should be noted that this refers to an additional component added to the carrier fluid of the alloy suspension. Its function is to improve the corrosion protection capability of the alloy particle suspension in acidic gas wells and high-salinity environments, and to avoid confusion with corrosion inhibitors in oxidizing solutions.

[0110] (4) Slow-release expansion heat source material: 120 kg of CaO / MgO composite microcapsule powder. The CaO / MgO composite microcapsule powder needs to be premixed with the reducing solution before subsequent use. The preparation method of the CaO / MgO microcapsule powder is as follows: Step 1: Weigh 26.7 kg of CaO powder and 13.3 kg of MgO powder at a mass ratio of 2:1 and mix them to obtain a mixed powder; add 16 kg of PLA to 200 L of dichloromethane and stir magnetically at 500 rpm for 2 hours at room temperature until completely dissolved to obtain a PLA solution with a mass concentration of 8% and a viscosity of about 30 mPa·s.

[0111] Step 2: Disperse 40 kg of the mixed powder in 200 L of 8% PLA solution, sonicate for 10 min, then stir at 400 rpm for 2 h at room temperature to ensure PLA uniformly coats the powder surface, followed by spray drying. A Buchi B-290 cryogenic spray drying system was used, with an inlet air temperature of 90℃ and an outlet air temperature of 45℃ (nitrogen closed-loop circulation, flame retardant), a peristaltic pump at 15%, and an exhaust fan at 100%, yielding CaO / MgO microcapsule powder of 80 μm-200 μm. The yield was approximately 95%, and the PLA shell thickness was 8-12 μm.

[0112] This embodiment also provides a construction method, the operation steps of which are as follows: Step 1 (Pre-flushing): Pump 10m into the target well section 3 The pre-rinse solution contains 1.0 wt% EDTA, 0.5 wt% EDTMP, and 0.3 wt% H2S scavenger (1,3,5-triazine-2,4,6-triamine), with a discharge rate of 0.4 m³ / min. 3 / min, thoroughly removes residual H2S and polyvalent metal ions from the target layer.

[0113] Step 2 (packer setting): Set the bridge plug at a well depth of 4210m as a lower support to ensure that molten metal fills the 4210m~4180m section (a total of 30m of sealing length).

[0114] Step 3 (Alloy Suspension Injection): Pump 500 kg of alloy suspension into the 4180 m~4210 m section through the suspension channel 16 of the coaxial continuous tubing, with a displacement of 0.20 m³ / s. 3 / min.

[0115] Step Four (Dual-Liquid Heat Source Injection and Downhole Mixing): 600 kg of oxidizing fluid is pumped in through the outer annular channel, and 700 kg of reducing fluid (containing CaO / MgO microcapsule powder) is pumped in through the inner pipe channel. The solutions are then mixed in a downhole static mixer (located at 4205 m). The oxidizing fluid discharge rate is 0.13 m³ / h. 3 / min, reducing solution displacement is 0.16m 3 / min.

[0116] Step 5 (Pump shutdown and well shut-in reaction): The downhole temperature rises from 138℃ to a peak of 192℃ (reached at approximately 5.5 hours), and the peak temperature is maintained for about 150 minutes; the first 60 minutes are mainly driven by the reaction of H2O2 and Na2S2O5, and the latter 90 minutes are maintained by the slow release of CaO / MgO hydration reaction.

[0117] Step 6 (Alloy Melting-Flowing-Cross Filling): The alloy core melts at a temperature above 175°C. Under the influence of gravity and expansion pressure, the liquid metal flows into the microcrack zone (50μm~200μm wide, 12m longitudinally extended). Short fiber particles bridge the wider cracks before melting, improving the filling efficiency.

[0118] Step 7 (Synergistic effect of alloy solidification and hydration expansion): When the temperature drops below 155℃, the alloy solidifies and expands in volume by about 0.8%; at the same time, the Ca(OH)2 / Mg(OH)2 hydration products continue to expand on the outside of the alloy phase (linear expansion rate of about 1.5%~2.5%), forming a composite structure of "dense metal core + inorganic expansion shell".

[0119] Step 8 (Flowback and Sealing Verification): Open the well and flow back approximately 12m³ of Na₂SO₄ / NaHSO₄ mixed brine byproducts. 3 The backflow liquid was neutralized and discharged in compliance with standards; the H2O2 concentration of the reaction residue was tested to be <10mg / L (the reducing agent was slightly in excess to ensure that the oxidant was completely consumed). The sealing test was conducted by maintaining a nitrogen pressure of 80MPa for 60min, with a pressure drop of <0.5MPa, indicating that the sealing was qualified.

[0120] The Bi-Sn-X alloy sealing composite medium prepared in this embodiment was used to repair the abandoned high-sulfur gas well, achieving permanent sealing of the well section. The sealing body consists of a Bi-Sn-Sb metallic phase (center) and a Ca(OH)2 / Mg(OH)2 / Na2SO4 inorganic phase (outer edge), with a density >99% and a porosity <0.3%. Evaluation by H2S / CO2 accelerated corrosion simulation experiments (180℃, 20MPa, 12vol% H2S, 6vol% CO2, for 90 days) showed that the corrosion weight loss rate of the sealing body was <0.05wt%, and the extrapolated long-term sealing life of 100 years is reliable. The total cost of single-well sealing is approximately RMB 560,000, which is more than 60% lower than the conventional multi-stage cementing + bridge plug scheme (approximately RMB 1.2 million to 1.5 million).

[0121] Example 3 This embodiment provides a Bi-Sn-X alloy sealing composite medium, which is composed of a reducing liquid, an oxidizing liquid, a Bi-Sn-X alloy composite material, and a slow-release expansion heat source material.

[0122] (1) The total mass of the oxidizing solution is 200 kg, which consists of the following components: 40 kg H2O2; 3.0 kg benzotriazole corrosion inhibitor; 0.6 kg HPAM thickener; 0.6 kg sodium pyrophosphate stabilizer; and 155.8 kg deionized water. In this embodiment, the H2O2 is 35 wt% industrial grade, that is, the mass of pure H2O2 is 14 kg.

[0123] (2) The total mass of the reducing solution is 272.84 kg, which is composed of the following components: 54.6 kg Na2SO3 (industrial grade ≥97%): (molar number approximately 420.33 mol, n(SO3) 2- ):n(H2O2)≈1.02:1); 0.55kg ATMP scale inhibitor; 5.46kg pH buffer; 1.36kg EDTA-Na4 chelating agent; 210.87kg deionized water. The pH buffer consists of 2kg Na2HPO4 and 3.46kg NaH2PO4.

[0124] (3) The mass of the Bi-Sn-In alloy composite material is 47.3 kg; in this embodiment, the preparation method of the Bi-Sn-In alloy composite material is the same as that in Example 1. The difference is that in this embodiment, when the Bi-Sn-In alloy composite material is prepared into an alloy suspension and then transported, the mass concentration of the Bi-Sn-In alloy composite material in the alloy suspension is 60%, and the mass of the solvent (a 5% xanthan gum aqueous solution) is 31.53 kg.

[0125] (4) Slow-release expansion heat source material: 23.6 kg of CaO microcapsule powder. The CaO microcapsule powder needs to be premixed with the reducing solution before subsequent use. The preparation method of CaO microcapsule powder is the same as in Example 1.

[0126] Example 4 This embodiment provides a Bi-Sn-X alloy sealing composite medium, which is composed of a reducing liquid, an oxidizing liquid, a Bi-Sn-X alloy composite material, and a slow-release expansion heat source material.

[0127] (1) The total mass of the oxidizing solution is 200 kg, which consists of the following components: 100 kg H2O2; 0.4 kg benzotriazole corrosion inhibitor; 2.0 kg HPAM thickener; 0.1 kg sodium pyrophosphate stabilizer; and 97.5 kg deionized water. In this embodiment, the H2O2 is 35 wt% industrial grade, that is, the mass of pure H2O2 is 35 kg.

[0128] (2) The total mass of the reducing solution is 326.87 kg, which is composed of the following components: 145.09 kg Na2SO3 (industrial grade ≥97%): (molar number approximately 714 mol, n(SO3) 2- ):n(H2O2)≈1.10:1); 3.27kg ATMP scale inhibitor; 1.63kg pH buffer; 0.33kg EDTA-Na4 chelating agent; 172kg deionized water. The pH buffer consists of 0.63kg Na2HPO4 and 1kg NaH2PO4.

[0129] (3) The mass of the Bi-Sn-In alloy composite material is 156.7 kg; in this embodiment, the preparation method of the Bi-Sn-In alloy composite material is the same as that in Example 1. The difference is that in this embodiment, when the Bi-Sn-In alloy composite material is prepared into an alloy suspension and then transported, the mass concentration of the Bi-Sn-In alloy composite material in the alloy suspension is 75%, that is, the mass of the solvent (a 5% xanthan gum aqueous solution) is 52.2 kg.

[0130] (4) Slow-release expansion heat source material: 104.5 kg of CaO microcapsule powder. The CaO microcapsule powder needs to be premixed with the reducing solution before subsequent use. The preparation method of CaO microcapsule powder is the same as in Example 1.

[0131] For wellbore sections requiring repair that are relatively short, have small fractures, or have high well temperatures, a lower alloy dosage and a lower heat source dosage can be used for repair, such as the Bi-Sn-X alloy sealing composite medium provided in Example 3. If the wellbore to be repaired has a low well temperature, a large plugging volume, or requires higher heat release, then a higher alloy dosage and a higher heat source dosage are needed, such as the Bi-Sn-X alloy sealing composite medium provided in Example 4. This invention is not limited here; the appropriate medium can be selected based on the actual situation.

[0132] It should be noted that due to wellbore corrosion products and the presence of polyvalent ions in formation water, such as metal ions (Fe), 3+ Ca 2+ Ba 2+ Factors such as high temperature (50℃), strong acid (pH<4), strong alkali (pH>10), light, and rough surface can all cause hydrogen peroxide to decompose prematurely during transportation, producing O2 bubbles and forming pores underground, and the heat release is uncontrollable.

[0133] Based on this, the present invention adds a chemical stabilizer (such as sodium pyrophosphate or sodium stannate) to the oxidation solution to complex heavy metals and inhibit the homogeneous decomposition of H2O2. For example, after adding 0.2% sodium stannate, the decomposition rate of 35wt% H2O2 at 50℃ for 4 hours decreased from 8.2% to 0.6%. During construction, a pre-flushing step is first performed to remove Fe from the formation. 3+ Ca 2+ Ba 2+ Then, the addition of a chelating agent to the reducing solution can further chelate the Fe dissolved from the wellbore. 3+ Eliminate the catalyst source. A pH buffer controls the system pH at 6-9 (preferably 7.5-8.2), ensuring H2O2 remains within its most stable range. The corrosion inhibitor forms an adsorption film on the inner walls of the casing and coiled tubing, reducing Fe... 3+Dissolution. The thickener provides physical isolation, reducing convective mass transfer and the merging of evolved oxygen bubbles by increasing viscosity. Furthermore, the oxidation liquid storage tank 1 in this invention is made of 316L stainless steel with passivation treatment, equipped with a cooling jacket, and the storage temperature is controlled at 5-25℃, kept dark and sealed. A low-shear paddle agitator is installed inside the tank for intermittent stirring at 50 rpm to prevent localized overheating. The high-pressure injection pump group 4 uses a plunger-type diaphragm pump, with the pump body and H2O2 contact parts made of PTFE. The inner wall of the coiled tubing 5 is lined with epoxy. During coaxial transport, the entire process takes less than 3 hours, the wellbore temperature field is less than 78-138℃ before mixing, and H2O2 is isolated from the wellbore formation when flowing in the annular channel 14. The thickener makes its flow state a plug flow, and the oxygen produced by decomposition is soluble in the liquid phase and discharged with the flowback 11, without forming pores in the alloy. Example 1 shows that the measured residual H2O2 in the flowback liquid is less than 50 mg / L, proving that it did not decompose in large quantities prematurely.

[0134] The above-described embodiments are merely preferred embodiments of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various improvements and substitutions without departing from the principles of the present invention, and these improvements and substitutions should also be considered within the scope of protection of the present invention. Therefore, the scope of protection of this invention should be determined by the scope of the claims.

Claims

1. A Bi-Sn-X alloy sealing composite medium, characterized in that, This includes oxidizing solutions, reducing solutions, Bi-Sn-X alloy composite materials, and slow-release expansion heat source materials; The oxidizing solution is composed of the following components by mass percentage: 20%~50% hydrogen peroxide, 0.2%~1.5% corrosion inhibitor, 0.3%~1.0% thickener, 0.05%~0.3% stabilizer, and the remainder is water, totaling 100%. The reducing solution consists of the following components by mass percentage: 20%~50% sulfite, 0.2%~1.0% scale inhibitor, 0.5%~2.0% pH buffer, 0.1%~0.5% chelating agent, and the remainder is water, totaling 100%. Bi-Sn-X alloy composite material is a Bi-Sn-X alloy core as the core body, which is coated with a metal oxide layer, an organic film and a reinforcing film from the inside out; X is selected from one or more of In, Ag, Cu, Zn and Sb, and the melting point of Bi-Sn-X alloy composite material is 80℃~160℃. The slow-release expansion heat source material is CaO microcapsule powder and / or MgO microcapsule powder; The molar ratio of anion to hydrogen peroxide in sulfite is 1.02~1.10:1; The amount of Bi-Sn-X alloy composite material added is 10% to 30% of the total mass of the oxidizing and reducing solutions; The amount of slow-release expansion heat source material added is 5% to 20% of the total mass of the oxidizing liquid and the reducing liquid.

2. The Bi-Sn-X alloy sealing composite medium according to claim 1, characterized in that, The organic film in the Bi-Sn-X alloy composite material is polyethylene wax or paraffin wax; the reinforcing film is epoxy resin film or polylactic acid film.

3. The Bi-Sn-X alloy sealing composite medium according to claim 1, characterized in that, The Bi-Sn-X alloy core is one or more of the following: granular Bi-Sn-X alloy core, rod-shaped Bi-Sn-X alloy core, microspherical Bi-Sn-X alloy core, and fibrous Bi-Sn-X alloy core; The particle size of the granular Bi-Sn-X alloy core is 50μm~2000μm; The aspect ratio of the rod-shaped Bi-Sn-X alloy core is 3~20; The diameter of the microspherical Bi-Sn-X alloy core is 100μm~500μm; The fibrous Bi-Sn-X alloy core has a diameter of 100μm~300μm and a length of 1mm~5mm.

4. The Bi-Sn-X alloy sealing composite medium according to claim 3, characterized in that, The Bi-Sn-X alloy core consists of the following components by mass percentage: 60%~80% granular Bi-Sn-X alloy core, 10%~30% rod-shaped Bi-Sn-X alloy core, and the remainder is fibrous Bi-Sn-X alloy core, totaling 100%.

5. The Bi-Sn-X alloy sealing composite medium according to claim 1, characterized in that, The corrosion inhibitors are imidazoline quaternary ammonium salts or benzotriazoles; The thickener is partially hydrolyzed polyacrylamide or xanthan gum; The stabilizer is sodium pyrophosphate or sodium stannate.

6. The Bi-Sn-X alloy sealing composite medium according to claim 1, characterized in that, The sulfite is one or more of sodium sulfite, sodium bisulfite, and sodium metabisulfite; The scale inhibitor is aminotrimethylenephosphonic acid or ethylenediaminetetramethylenephosphonic acid; The pH buffer is a combination of sodium dihydrogen phosphate and disodium hydrogen phosphate or a combination of boric acid and borax. The chelating agent is tetrasodium ethylenediaminetetraacetate or aminotriacetic acid.

7. A wellbore repair method, characterized in that, Repair is performed using the Bi-Sn-X alloy sealing composite medium according to any one of claims 1 to 6, and the repair method is as follows: Inject a pre-flushing solution containing chelating agents and scale inhibitors into the target layer to remove oil and polyvalent metal ions; after cleaning, deliver the Bi-Sn-X alloy composite material to the target sealing layer. The reducing agent and the slow-release expansion heat source material are mixed to form a mixed liquid. The mixed liquid and the oxidizing agent are transported to the bottom of the well for mixing. During the mixing process, the reducing agent and the oxidizing agent in the mixed liquid undergo an oxidation-reduction reaction that releases heat, and the slow-release expansion heat source material also releases heat, causing the Bi-Sn-X alloy core to melt and form a Bi-Sn-X alloy molten liquid. Driven by the downhole pressure difference and gravity, the Bi-Sn-X alloy molten liquid seeps into the wellbore area to be repaired. After solidification and expansion, it forms a composite plugging body, completing the plugging.

8. The wellbore repair method according to claim 7, characterized in that, The method for conveying the Bi-Sn-X alloy composite material is as follows: The Bi-Sn-X alloy composite material is prepared into an alloy suspension in a xanthan gum aqueous solution. The mass concentration of the Bi-Sn-X alloy composite material in the alloy suspension is 60%~75%; the discharge rate of the alloy suspension is 0.15~0.20 m³ / s. 3 / min; the discharge rate of the oxidizing liquid is 0.10~0.13m 3 / min; the discharge rate of the mixed liquid is 0.11~0.16m 3 / min.

9. The wellbore repair method according to claim 7, characterized in that, Wellbore repair scenarios include cement sheath microcrack repair, casing-cement sheath microannulus repair, casing perforation repair, permanent sealing of abandoned wells, underground gas storage sealing layer repair, and compressed air energy storage wellbore sealing repair.

10. A wellbore repair system, characterized in that, include: A coaxial dual-liquid coiled tubing (5) is installed inside the casing (7) of the wellbore and extends along the inside of the casing (7) to above the target sealing section (8) downhole. The coaxial dual-liquid coiled tubing (5) is formed by coaxially sleeved outer tube (12) and inner tube (13). An annular channel (14) is formed between the inner wall of the outer tube (12) and the outer wall of the inner tube (13). An inner tube channel (15) is formed inside the inner tube (13). A suspension channel (16) is provided on one side of the outer tube (12). A blowout preventer (6) is provided above the coaxial dual-liquid coiled tubing (5). Oxidizing liquid storage tank (1), which is located on the ground, is used to store the oxidizing liquid as described in claim 8. The outlet of the oxidizing liquid storage tank (1) is connected to the first inlet of the high-pressure injection pump group (4) through the first pipeline. The first outlet of the high-pressure injection pump group (4) is connected to the annulus channel (14) through the wellhead blowout preventer (6). The reducing liquid storage tank (2) is located on the ground and is used to store the mixture as described in claim 8; the outlet of the reducing liquid storage tank (2) is connected to the second inlet of the high pressure injection pump group (4) through the second pipeline, and the second outlet of the high pressure injection pump group (4) is connected to the inner pipe channel (15) through the wellhead blowout preventer (6); Alloy suspension storage tank (3), which is located on the ground, is used to store the alloy suspension as described in claim 8; the outlet of the alloy suspension storage tank (3) is connected to the third inlet of the high pressure injection pump group (4) through a third pipeline, and the third outlet of the high pressure injection pump group (4) is connected to the suspension channel (16) through the wellhead blowout preventer (6). The downhole static mixer (9) has one end detachably connected to the bottom of the coaxial dual-liquid continuous tubing (5), and the other end is located at or above the target sealing section (8). The downhole static mixer (9) is provided with static mixing spiral blades (17), delayed mixing chamber (18), soluble diaphragm (19) and outlet nozzle (20) from top to bottom. The return pipeline (11) is located in the wellbore below the target sealing section (8) at one end and extends upward along the inside of the casing (7) at the other end, and is connected to the surface treatment assembly through the wellhead blowout preventer (6).